Final destination 5-film collection [videorecording (DVD)] - Wong, James, 1959-; Sawa, Devon, 1978-; Larter, Ali, 1976-; Smith, Kerr; Ellis, David R. (David Richard), 1952-2013; Cook, A. J., 1978-; Landes, Michael, 1972-; Winstead, Mary Elizabeth; Merriman, Ryan; Campo, Bobby, 1983-; VanSanten, Shantel, 1985-; Williamson, Mykelti; et al. (Warner Home Video, 2017)
Final destination: While boarding for a cross-country flight with friends, Alex has a premonition of the plane crashing. When he causes a ruckus and gets kicked off the flight, he and his friends watch in horror as the plane crashes, but Alex and his friends learn that they were fated to die on board the airplane, a fate that hunts them down one-by-one. Final destination 2: A teen with mild precognitive powers prevents a gruesome highway accident from killing seven strangers and must protect the ones she saved from Death. Final destination 3: A group of seven high school graduates manages to escape from a deadly roller-coaster disaster, only to discover that their own deaths have been only temporarily avoided. The final destination: When Nick manages to escape a gristly car wreck at a racetrack, he must figure out how to cheat death once and for all. Final destination 5: When one man's premonition saves him and a group of his coworkers from a suspension bridge collapse, they learn that they were never meant to survive the catastrophe and must find a way to escape Death's sinister agenda.